2013
DOI: 10.1097/mao.0b013e3182a36065
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Outcomes of Atresia Surgery Versus Osseointegrated Bone Conduction Device in Patients With Congenital Aural Atresia

Abstract: The OBCD has better hearing outcomes compared with atresiaplasty in patients with CAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…However, there are still some skin problems related with percutaneous devices, mainly in tropical countries where the weather is warm and humid. Also, many patients do not wish to use percutaneous devices for aesthetic reasons [19][20][21] . Recently, transcutaneous passive devices are being more frequently prescribed; it has been reported that they cause slight pressure irritation of the skin between the implants and the external base plate [22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still some skin problems related with percutaneous devices, mainly in tropical countries where the weather is warm and humid. Also, many patients do not wish to use percutaneous devices for aesthetic reasons [19][20][21] . Recently, transcutaneous passive devices are being more frequently prescribed; it has been reported that they cause slight pressure irritation of the skin between the implants and the external base plate [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the severity of the anomaly, several treatment options are to be considered in children presenting with such altered anatomy: surgical correction of the anomaly if feasible, amplification by means of a conventional hearing aid if possible or a bone conduction device (BCD) in all other cases, or conservatively monitoring the child’s development. When intervention is required, amplification of sound by means of a percutaneous BCD is associated with better audiological outcome than surgical intervention, especially in patients with considerable anatomic deviations [57]. …”
Section: Introductionmentioning
confidence: 99%
“…The most consistently reported measure of a successful hearing result was a SRT, PTA, or ABG less than 30 dB HL and average hearing gain [12]. All of our six articles included the results of ABG < 30 dB.…”
Section: Discussionmentioning
confidence: 96%
“…Lambert had proposed that some degradation in hearing outcomes does occur as patients with atresiaplasty are followed beyond the first postoperative year [11]. This finding was confirmed in many other studies [12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation